2017
DOI: 10.1007/s00259-017-3716-2
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival and response pattern of castration-resistant metastatic prostate cancer to multiple cycles of radioligand therapy using [177Lu]Lu-PSMA-617

Abstract: Patients with a positive response to RLT, regardless of the rate of decline, had a significantly longer median OS. Of the patients that did not show any response to the first cycle, 50% responded to the second or third cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
116
3
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 149 publications
(139 citation statements)
references
References 23 publications
16
116
3
4
Order By: Relevance
“…Thus, in accordance with Rahbar et al and results of the current study, the cumulative administered activity of PSMA‐RLT also seemed to correlate positively with survival. Similarly, other reports have suggested that all PSA decreases are reliable markers for predicting response and survival following PSMA‐RLT …”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Thus, in accordance with Rahbar et al and results of the current study, the cumulative administered activity of PSMA‐RLT also seemed to correlate positively with survival. Similarly, other reports have suggested that all PSA decreases are reliable markers for predicting response and survival following PSMA‐RLT …”
Section: Discussionmentioning
confidence: 61%
“…The radiolabeling, administration, and treatment procedures in this study were conducted using previously described methods . The median administered activity per cycle was 6.2 GBq (total range of 3.2‐7.5 GBq).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations